EXPRESSIVE SPEECH ON GITA WIRJAWAN'S YOUTUBE ACCOUNT: IS IT POSSIBLE TO MERITOCRACY IN THE MIDST OF MEDIOCRACY WITH ROCKY GERUNG AND TOM LEMBONG - Pertiwi Anggraini; Fatmawati (SOSIOEDUKASI, 2026)
This research is motivated by the importance of understanding the use of language in political communication in digital media, especially expressive speech that not only conveys information, but also shows the attitude and feelings of the speaker. The problem in this study is how the function of expressive speech is used in political discussions on YouTube and how it plays a role in building meaning and influencing the audience. This study aims to identify and analyze the function of expressive speech in Gita Wirjawan's YouTube video entitled "Is it possible to have a Meritocracy in the midst of mediocrity". The novelty of this research lies in the focus of the study that discusses digital political discussions that are open and interactive, and not only identifies the types of speech, but also examines the function and context of its use. This research uses a qualitative approach with a content analysis method. Data in the form of oral speech was obtained through listening and recording techniques, then analyzed through the stages of reduction, classification, and drawing conclusions. The results showed that there were 87 expressive speeches consisting of four main functions, namely criticizing (35 data), praising (28 data), satirizing (20 data), and thanking (4 data). The criticism function is the most dominant because the discussion that takes place is argumentative, while the praise function acts as a counterbalance so that communication continues to run well. The conclusion of this study shows that expressive speech does not only function as an expression of feelings, but also as a strategy in expressing opinions, building arguments, and influencing the audience's perspective in digital political discussions.